Evaluation of Antibodies against a Rubella Virus Neutralizing Domain for Determination of Immune Status - Cordoba, Patricia (American Society for Microbiology, 2000)
The protective immune responses against rubella virus (RV) are related to its neutralizing epitopes, an issue that is important to consider when assessing the immune status of patients with remote infection. In the present paper, we compare the antibodies detected by a synthetic-peptide-based enzyme immunoassay (EIA) with antibodies detected by the traditional technique of hemagglutination inhibition (HIA) in patients with remote RV infection. The synthetic peptide used as an antigen (SP15) represents a neutralizing epitope that corresponds to amino acids 208 to 239 of the E1 glycoprotein. The SP15-EIA was developed, all variables that affected the assay were standardized, and the test was validated using reference sera. Serum samples (n = 129) from patients with remote RV infection were tested by HIA and SP15-EIA. Discrepant sera were assayed by MEIA (IMX/Abbot). The comparison between HIA and SP15-EIA, taking HIA as the standard methodology for determining immune status, showed that SP15-EIA is very specific and sensitive for detecting protecting antibodies (specificity, 100%; sensitivity, 98.20%). This study demonstrates that antibodies against the neutralizing domain represented by SP15 would be important in the memory response after natural infection and may be a good tool in the determination of the true immune status of patients with remote infection with regard to RV.